Carrier dyeing of polyphenylene sulphide fabric with disperse dye. (9th November 2012) - Mao, Ya‐Hong; Guan, Yu; Zheng, Qing‐Kang; Liu, Qing‐Shu; Feng, Xi‐Ning; Wang, Xiu‐Xing
<x xml:space="preserve">Abstract</x> Polyphenylene sulphide is considered to be a high‐performance thermoplastic material and has been used in many areas over the past few decades. But the application of polyphenylene sulphide fabric used for protective clothing is limited because of difficulties in its dyeing and printing. In this work, carrier dyeing of polyphenylene sulphide fabric with disperse dye is discussed, and the effect of the structure of the carrier, dyeing temperature, dyeing time, usage of carrier and usage of dye on colour strength of the dyed sample and the percentage of dye exhaustion were investigated. In addition, the glass transition temperature, crystalline structure and orientation degree of treated polyphenylene sulphide fibre with benzyl benzoate were measured by differential scanning calorimetry, X‐ray diffraction analysis and velocity‐oriented tester, respectively. The results indicated that benzyl benzoate could increase the percentages of dye exhaustion and colour strength values, while at the same time reduce the glass transition temperature and orientation degree of the treated polyphenylene sulphide fibre. Thus, it would be beneficial to the diffusion of the dye molecules into the amorphous region of the fibre. Furthermore, the decrease of tensile strength and limiting oxygen index of the dyed polyphenylene sulphide sample was very little, and the colour fastness and levelness of the dyed polyphenylene sulphide samples were also satisfactory.